Pengaruh Kepala Sekolah Terhadap Mutu Lulusan di SMA Islam Parlaungan Waru Sidoarjo - S, Syafrijallah; M, Masfufah (Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out and provide input on the influence of school principals on the quality of graduates. This research problem was solved by observing and obtaining data through school academics at Parlaungan Waru Sidoarjo Islamic High School and processing the data obtained using formulas. The influence of the principal's leadership at Parlaungan Waru Sidoarjo Islamic High School is included in the very good category with a sample frequency of 13 people and a percentage of 81% with a mean score of 557. Improving the Quality of Graduates at Parlaungan Waru Sidoarjo Islamic High School is included in the very good category with a sample frequency of 13 people and percentage of 91%, with a mean score of 588%. There is an influence of the principal's leadership on the quality of graduates at Parlaungan Waru Sidoarjo Islamic High School with a significance value of 0.000, the comparison shows that 0.000 < 0.111 so H0 is rejected and Ha is accepted.